Characteristics of bacterial communities in rhizosphere and bulk soil in Fe-deficient citrus growing in coastal saline-alkali land - Jiang, Tianchi; Chen, Jiuzhou; Huang, Yu; Chang, Xiaoyan; Wu, Yuping; Liu, Gaoping; Wang, Runze; Xu, Kuan; Lu, Lingli; Lin, Haizhong; Tian, Shengke (Frontiers in Plant Science, 2024)
Aims Citruses often occur with imbalance in iron nutrition in coastal saline-alkali lands, which severely limits the yield and quality of the fruit. In the rhizosphere, the salt content plays a crucial role in reducing uptake of iron, as well as the activity and abundance of bacteria.However, few studies have explored how salt content affects the effectiveness of iron and the community structure of bacteria across different vertical spatial scales.Methods We investigated the citrus rhizosphere (0-30 cm) and bulk (0-60 cm) soil microenvironments of the coastal saline soil were analyzed using the 16S rRNA amplicon and inductively coupled plasma-optical emission spectroscopy.We found that the nutrient-related elements in the rhizosphere and bulk soil decreased with increasing soil depth, while the salinity-related elements showed the opposite trend. The nutrient-related element content in the rhizosphere was higher than that in the bulk, whereas the salinity-alkaline-related element content was lower than that in the bulk. The structure and diversity of bacterial communities are affected by the rhizosphere and soil depth. In the bulk, there are enriched bacteria such as WB1-A12, Nitrospiraceae and Anaerolineae that are tolerant to salt-alkali stress. In the rhizosphere, bacteria that promote plant nutrient absorption and secretion of iron carriers, such as Pseudomonas, Streptomyces, and Duganella, are prominent. Conclusions The soil depth and rhizosphere affect soil nutrients and saline alkali-related factors. Changes in soil depth and rhizosphere determine the structure and diversity of bacterial communities. Rhizosphere enhances iron absorption promoting bacteria to 删除的内容: In the rhizosphere, the salt content plays a 49 crucial role in the effectiveness of iron, as well as the activity 50 and abundance of bacteria 51 删除的内容: specific bacteria 52 4 alleviate iron deficiency stress in saline-alkali soils. Our results indicate that citrus roots maybe can resist the stress of iron deficiency in saline-alkali soils by enhancing iron absorption promoting bacteria.